The Covid-19 Pandemic—Opportunities for Circular Economy Practices Among Sewing Professionals in the City of Curitiba-Brazil - Corrêa, Harrison Lourenço; Corrêa, Daniela Gallon (Frontiers in Sustainability, 2021)
The pandemic that the world has been facing since Jan-2020 has promoted rapid changes in the form of consumption and service provision, besides the countless losses of human lives. Corporations, public organizations, and nations committed to healthcare have reinvented themselves in order to survive the period of massive crisis in the 21st century. Sectors such as aviation, transport, tourism, real estate, education, and many others have suffered overwhelming consequences in their business areas. In many countries, GDP forecasts have turned negative. But, if on the one hand, the prospects were negative, on the other, there were positive signs. Traffic reduction in large cities, reflecting an improvement in air quality; transformation in the mode of information consumption with an increase in remote school classes; democratization of knowledge, with networks publishing books for free; recycling, remanufacturing, and reuse practices strengthening the principles of economic circularity. During the virus spread period of the new coronavirus, many enterprises emerged or were transformed in order to ensure, at least initially, the supply of personal protective equipment for health professionals (masks and face shields). Reusing raw materials in their production lines, companies and volunteers produced masks for mandatory use by the population of some countries such as Brazil. This brief period energized an economy that until then seemed to be dormant. In view of this scenario that took shape in the world, the present study aimed to assess how this pandemic affected sewing professionals’ enterprises, contributing to an income generation and to a possible sustainable practice. The survey of enterprise circularity was carried out in a quantitative way, through a questionnaire and interviews. Results obtained by fabric remnants mass balance indicated some level of circularity in the production mode of seamstresses during the pandemic. The challenge, however, is to maintain this productive process to manufacture other artifacts.